SPORT AS A MEANS OF SOCIAL INCLUSION AND EXCLUSION. INTRODUCTION TO THE SPECIAL ISSUE OF SOCIETY REGISTER - Honorata Jakubowska (Society Register)
This issue consists of nine articles, followed by two books reviews. The contributions reveal that the issues of inclusion and exclusion can be analysed in very different contexts of the sports field, with relation to different sports disciplines, and different groups and countries. The authors provide analysis of their own research, analysis of secondary data, as well as theoretical frameworks and a large number of references. The topics raised and case studies analysed are predominantly very recent.